POLA GARAPAN LAGU œTIM TAM TUM MENGGUNAKAN ANSAMBEL CAMPURAN PADA SISWA EKSTRAKURIKULER SMP NEGERI 15 PALEMBANG - Sepdwiko, Deria; Yelli, Nofroza (Universitas Negeri Medan, 2020)
In writing this research the writer discusses the pattern of cultivating songs œTIM TAM TUM Using Mixed ensembles for exstracurriculer students of SMP 15 Palembang.This study aims to determine how the pattern form the Tim Tam Tum song composed by using a mixed ensemble. The data collection techniques used were, observation, interview, and documentation techniques. The method used in this research is a qualitative descriptive method. The results of this study are analyzed to become a research report that has an output, target, namely being published in a scientific journal and used as teaching material in related subjects, especially in the field of music. The media instruments used in this mixed ensemble are: percussion , instruments, drum, symbal, guitar, bass, pianica,and violin, meanwhile, the musical form of the technique uses the yunisono technique.